Improving the Quality of Hotel Visitor Services at three- to five-star hotels in Bandung - Annita Jannah (Majalah Bisnis & IPTEK, 2026)
This research addresses the critical issue of suboptimal service quality in three- to five-star hotels in Bandung. The study aims to investigate the relationship between service quality and visitor loyalty among these hotels. Data collected from a survey of 210 visitors, all of whom have visited at least three times, is employed to test the research hypotheses. The analysis utilizes Structural Equation Modeling with Partial Least Squares (PLS SEM) to evaluate the data. The findings reveal that interaction quality, physical environment quality, and outcome quality significantly impact visitor satisfaction and loyalty. This study is novel in highlighting specific aspects of service quality that directly enhance customer satisfaction in the hotel sector. The implications of this research suggest that hotel management should focus on improving these service quality dimensions to foster greater customer loyalty and satisfaction, ultimately leading to better business performance.